Functional categories and parametric variation - Ouhalla, Jamal, 1961- (Theoretical linguistics (Routledge (Firm)), 1991)
From within the context of the Principles and Parameters framework put forward by Chomsky and others, Jamal Ouhalla develops the argument that much of what we understand by the term grammar involves functional categories.